A synthetic opioid vaccine attenuates fentanyl-vs-food choice in male and female rhesus monkeys. (1st January 2021) - Townsend, E. Andrew; Bremer, Paul T.; Jacob, Nicholas T.; Negus, S. Stevens; Janda, Kim D.; Banks, Matthew L.
Highlights: A fentanyl-targeted vaccine decreases choice of IV fentanyl over a food alternative in male and female rhesus monkeys. Effectiveness of the fentanyl vaccine was similar to continuous buprenorphine treatment, but with a longer duration of action. This vaccine formulation was stored at room temperature without any apparent degradation in its effectiveness. Abstract: Aim: Opioid-targeted vaccines are under consideration as candidate Opioid Use Disorder medications. We recently reported that a fentanyl-targeted vaccine produced a robust and long-lasting attenuation of fentanyl-vs-food choice in rats. In the current study, we evaluated an optimized fentanyl-targeted vaccine in rhesus monkeys to determine whether vaccine effectiveness to attenuate fentanyl choice translated to a species with greater phylogenetic similarity to humans. Methods: Adult male (2) and female (3) rhesus monkeys were trained to respond under a concurrent schedule of food (1 g pellets) and intravenous fentanyl (0, 0.032−1 μg/kg/injection) reinforcement during daily 2 h sessions. Fentanyl choice dose-effect functions were determined daily and 7-day buprenorphine treatments (0.0032−0.032 mg/kg/h IV; n = 4–5) were determined for comparison to vaccine effects. Subsequently, a fentanyl-CRM197 conjugate vaccine was administered at week 0, 3, 8, 15 over a 29-week experimental period during which fentanyl choice dose-effect functions continued to be determined daily. Results: Buprenorphine significantly decreased fentanyl choice and reciprocally increased food choice. Vaccination eliminated fentanyl choice and increased food choice in four-of-the-five monkeys. A transient and less robust vaccine effect was observed in the fifth monkey. Fentanyl-specific antibody concentrations peaked after the third vaccination to approximately 50 μg/mL while anti-fentanyl antibody affinity increased to a sustained low nanomolar level. Conclusion: These results translate fentanyl vaccine effectiveness from rats to rhesus monkeys to decrease fentanyl-vs-food choice, albeit with greater individual differences observed in monkeys. These results support the potential and further clinical evaluation of this fentanyl-targeted vaccine as a candidate Opioid Use Disorder medication.